2004
DOI: 10.1002/em.20083
|View full text |Cite
|
Sign up to set email alerts
|

RAD6gene is involved in heat shock induction of bleomycin resistance inSaccharomyces cerevisiae

Abstract: Cells react to environmental and endogenous challenges such as high temperature, reactive oxygen species, DNA damage, and nutrient starvation by activating several defense mechanisms known as stress responses. An important feature is the overlap between different stress responses that contributes at least in part to the phenomenon of cross-protection. We previously demonstrated that pretreatment with a heat shock (HS) induces resistance to the lethal and mutagenic effects of the antineoplastic drug Bleomycin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…On the other side, the lethal additivity and the low mutagenic interaction observed in case of Pt þ E combination (Figures 2c, 3b, 4b, and 5b) can be explained by independent error-prone processing of induced damage, most probably error-prone excision repair (MMR), NHEJ and postreplicative errorprone repair (Keszenman et al 2005). The contribution of NHEJ in the repair of DNA damage produced by etoposide in Saccharomyces has been previously determined (Malik et al 2006).…”
Section: Discussionmentioning
confidence: 94%
“…On the other side, the lethal additivity and the low mutagenic interaction observed in case of Pt þ E combination (Figures 2c, 3b, 4b, and 5b) can be explained by independent error-prone processing of induced damage, most probably error-prone excision repair (MMR), NHEJ and postreplicative errorprone repair (Keszenman et al 2005). The contribution of NHEJ in the repair of DNA damage produced by etoposide in Saccharomyces has been previously determined (Malik et al 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Escherichia coli it has been shown that the presence of antibiotic resistance genes probably has been induced by adaptation to stress (like thermal stress) as tolerance towards antibiotics underlies similar mechanisms as tolerance towards heat (Cruz-Loya et al, 2019) This could potentially explain why a gene encoding a bleomycin resistance protein was upregulated at elevated temperatures in the cyanobiont of P. britannica. In addition, Keszenman et al (2000Keszenman et al ( , 2005 have demonstrated that the upregulation of bleomycin resistance genes is a side effect of heat stress in S. cerevisiae, as the yeast cells proved to be resistant to bleomycin treatment after having been exposed to heat stress. This correlation between heat stress and bleomycin resistance is probably the result of cross-linking of DNA repair mechanisms (Keszenman et al, 2000(Keszenman et al, , 2005.…”
Section: Photobiont Genes/temperaturementioning
confidence: 99%
“…In addition, Keszenman et al (2000Keszenman et al ( , 2005 have demonstrated that the upregulation of bleomycin resistance genes is a side effect of heat stress in S. cerevisiae, as the yeast cells proved to be resistant to bleomycin treatment after having been exposed to heat stress. This correlation between heat stress and bleomycin resistance is probably the result of cross-linking of DNA repair mechanisms (Keszenman et al, 2000(Keszenman et al, , 2005. A potential role of bleomycin-resistance genes in DNA repair has already been proposed in previous studies on E. coli (Blot et al, 1991).…”
Section: Photobiont Genes/temperaturementioning
confidence: 99%
“…Quantification is possible after laser absorbance analysis [14]. Estimation of mean values of induced DNA double-strand breaks (DBSs) and of corresponding standard deviations were based on the Poisson distribution as: −L Ix/Io, where Ix corresponds to the integral (surface) of a given chromosomal band in the densitograms after treatment and Io is the integral of the same chromosomal band in the respective control sample [9,[13][14][15][16].…”
Section: Chromosomal Dna Analysismentioning
confidence: 99%